Study of the state of the art techniques for rotor noise suppression from microphone mounted on UAV - Chua, Zhen Long (2017)
An Unmanned Aerial Vehicle when mounted with a beamformer can serve as a security surveillance platform for agencies or organization. Beamformer is a spatial filter used to collect acoustic signals from a specific direction which allow it to pick up signal from the ground. However the above Unmanned Aerial Vehicle application poses certain problem. The noise as well as the speech signal will be picked up by the microphone which is not desired.